Concomitant infection of haemogregarina sp. and staphylococcus aureus in free-living yellow-spotted river turtle (Podocnemis Unifilis): Case report - Úngari, Letícia Pereira [UNESP]; Santos, André Luiz Quagliatto; Paiva, Guilherme Carrara Moreira; Mota, Kelem Cristina Pereira; Borges, Lizandra Ferreira de Almeida; Cury, Márcia Cristina (Universidade Federal do Paraná, 2018)
A male adult yellow-spotted river turtle Podocnemis unifilis (Chordata: Testudines: Podocnemididae) was captured during field collections. Blood sample was collected for haemoparasite screening by conventional light microscopy. Morphometric and morphological analyzes of the parasite developmental stages were performed in the blood extensions, as well as the parasitemia intensity. Gametocytes of hemogregarines and innumerable bacterial cells were observed. To identify the bacteria present, a culture was performed and the presence of Staphylococcus aureus was observed. It was concluded that a co-infection of Staphylococcus aureus (Firmicutes: Bacillales: Staphylococcaceae) and Haemogregarina sp. (Apicomplexa: Adeleina: Haemogregarinidae) was observed in this free-living yellow-spotted river turtle Podocnemis unifilis.

Durante coletas de campo, um macho adulto de tracajá Podocnemis unifilis (Chordata: Testudines: Podocnemididae) foi capturado. Amostra de sangue foi colhida para pesquisa de hemoparasitos pela microscopia óptica convencional. Nas extensões sanguíneas foram realizadas análises morfométricas e morfológicas das formas evolutivas encontradas, bem como o cálculo da parasitemia. Foram observados gametócitos de hemogregarinas e inúmeras células bacterianas. Para identificação das bactérias presentes foi realizada cultura, sendo observada a presença de Staphylococcus aureus. Conclui-se que havia co-infecção por Staphylococcus aureus (Firmicutes: Bacillales: Staphylococcaceae) e Haemogregarina sp. (Apicomplexa: Adeleina: Haemogregarinidae) no tracajá Podocnemis unifilis.
Infecção concomitante de Haemogregarina sp. e Staphylococcus aureus em tracajá (Podocmenis unifilis) de vida livre: Relato de caso
Keywords: Co-infection; Co-infecção; Hemogregarinas; Hemogregarines; Occurrence; Ocorrência; Podocnemis unifilis; Staphylococcus aureus